2019
DOI: 10.1097/aln.0000000000002772
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Contamination of Medication Vials Accessed with Sterile Needles and Syringes

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Health care–associated hepatitis C virus outbreaks from contaminated medication vials continue to be reported even though most practitioners deny reusing needles or syringes. The hypothesis was that when caring for hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Sample size was based on similar previous studies. 4,15,16 All data are representative of 3 independent experiments with 3 independent replicates per experiment (n = 9). All data points represent 3 independent measurements per replicate, and error bars represent standard deviation (SD).…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was based on similar previous studies. 4,15,16 All data are representative of 3 independent experiments with 3 independent replicates per experiment (n = 9). All data points represent 3 independent measurements per replicate, and error bars represent standard deviation (SD).…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] A study by van Vlymen demonstrated that poor hand hygiene practices inadvertently cause tiny amounts of hepatitis C virus to be placed on the outside of a medication vial, leading to further contamination and infection. [58] Improved frequency and quality of environmental cleaning of the AWE following induction and emergence of anesthesia have reduced the proportion of environmental sites reaching the 100 CFU threshold associated with high-risk stopcock transmission events. [59] This involved post-induction cleaning with a surface disinfection wipe containing both a quaternary ammonium compound and alcohol along with improved organization with designation of clean and dirty spaces, decreasing the proportion of sites reaching or exceeding 100 CFU from > 40 to 12%.…”
Section: The Anesthesia Providermentioning
confidence: 99%
“…Internationally, injection of opioids like heroin and fentanyl has increased during the opioid epidemic and is an increasingly prevalent risk factor for HBV and HCV infection 7‐11 . Even in the absence of visible blood, HBV can remain infectious on environmental surfaces for at least 7 days, 6,12,13 and HCV can live in dried blood spots to be infectious from days to weeks 14‐16 . The risk that a nonimmune individual with an untreated percutaneous exposure to an HBV‐infected source will seroconvert is as high as 30%; by contrast, the risk for HCV is 1.8% 17 …”
Section: Epidemiologymentioning
confidence: 99%